(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study ascertained the level of acquisition of entrepreneurial innovation skills by postgraduate business education students for self-sustainability in Rivers State. One research question aided the study and one hypothesis was tested at 0.05 level of significance. The design of the study was descriptive survey. A total of 298 business education postgraduate students in two Rivers State universities made up the population. 44 postgraduate business education students in Rivers State University and 254 postgraduate business education students in Ignatius Ajuru University of Education in Rivers State. The instrument for data collection was a structured questionnaire tittled: Entrepreneurial Innovation Skills Acquisition Questionnaire (EISAQ). Three experts validated the instrument and a reliability test using Cronbach Alpha method yielded an internal consistency index of 0.86. Mean ratings and standard deviation were used to answer the research question while t-test for large group mean was used to test the hypothesis at a significance at 0.05. The findings of the study revealed that business education postgraduate students acquired moderate level of entrepreneurial innovation, skills for selfsustainability. The findings of the study also revealed that postgraduate business education students in Rivers State University and Ignatius Ajuru University of Education did not differ significantly regarding the level of acquisition of entrepreneurial innovation skills for selfsustainability. Based on the findings, conclusion was drawn that entrepreneurial innovation skills acquired by postgraduate business education students for self-sustainability was necessary. Lack or absence of these skills negatively affected graduates embarking on any business ventures was led to business failures. It was recommended among others that graduate students of business education must be able to maintain entrepreneurial characteristics and traits by finding solution to problems that arise when operating business ventures. The courage to continue the business will lead to success and self-sustainability. Entrepreneurship centres in universities or other tertiary institutions in Nigeria must be equipped and utilized to assist institutions to bridge the gap created by the theoretical nature of entrepreneurial programmes in institutions.